Diversity of Food Consumption and the Event of Stunting in Children in the Lowlands of South Kalimantan, Indonesia - Ahmad Suhaimi (Green Publisher Indonesia, 2022)
This study aims to determine the diversity of food consumption and its relationship with the incidence of stunting in children under five in the lowlands of South Kalimantan, Indonesia. The research location is in Batang Alai Selatan District, Hulu Sungai Tengah Regency. This research is an associative type of research using primary and secondary data sourced from respondents, and BPS Hulu Sungai Tengah Regency. The diversity of food consumption in stunting toddlers was first carried out with a 24-hour food recall and analyzed using the Expected Food Pattern (PPH) approach. The relationship between the diversity of food consumption and the incidence of stunting in children under five was carried out by Chi Square analysis. The results showed that the PPH score for the diversity of food consumption under five reached 76.44, indicating that the criteria were less diverse because it was still dominated by the grain food group (52.8%) and animal food (38.3%). The results of the Chi Square analysis show that the diversity of food consumption with the incidence of stunting in children under five in the study area has an Asymp value. Sig. (2-sided) 0.000 < 0.05, and the calculated Chi Square value is 20.17 > Chi Square table 3.841, it can be concluded that there is a relationship between the diversity of food consumption and the incidence of stunting in children under five.